PEAR1 rs12041331 polymorphisms and the risk of adverse cardiovascular outcomes in patients with acute coronary syndrome and/or percutaneous coronary intervention: a systematic review and meta-analysis. (25th November 2020) - Xu, K; Zheng, X; Cai, J; Chan, N; Shen, L; He, B
Abstract: Background: Platelet endothelial aggregation receptor-1 (PEAR1), expressed in endothelium, platelets, and other tissues, is a platelet transmembrane tyrosine kinase receptor involved in platelet aggregation and platelet-platelet contact. The minor allele (A) in intron 1 of the PEAR1 gene (rs12041331, G>A) is associated with an reduced PEAR1 protein expression and suppressed platelet aggregation response toward multiple agonists. But current evidences on the association between PEAR1 rs12041331 polymorphisms and cardiovascular outcomes in patients with acute coronary syndrome (ACS) and/or percutaneous coronary intervention (PCI) are discordant. Purpose: To characterize and quantify the association between PEAR1 rs12041331 polymorphisms and cardiovascular outcomes in patients with ACS and/or PCI. Methods: We conducted a systematic review and meta-analysis by searching MEDLINE via PubMed, EMBASE, Cochrane Central Register of Controlled Trials, SinoMed, CNKI, and Wanfang Data before Dec 7, 2019 to identify studies evaluating the association between PEAR1 rs12041331 polymorphisms and cardiovascular outcomes in patients with ACS and/or PCI. The primary outcome was the major adverse cardiovascular outcomes (MACEs) defined by each study. We adopted the Mantel-Haenszel method to calculate the relative risks (RRs) with 95% confidence intervals (CIs) and the corresponding P values using the random effect model. To assess the effect of ethnicity, we performed the subgroup analyses per ethnic population using the fix effect model. Results: Among 542 citations identified along with 1 from additional sources, we included 4 studies, which documented 218 MACEs in 8180 patients. The A allele frequency in each study was comparable with that reported in the 1000 Genome Project, but varied among ethnic populations, that is 45.8% in East Asians, 46.5% in American Africans, and 9.2% in Caucasians, adopted from the 1000 Genome Project. A-allele carriers are associated with a 54% increase in MACEs than non-A-carriers (RR, 1.54; 95% CI, 1.10–2.16; P=0.01) with a low but non-significant heterogeneity. Subgroup analyses showed that A-allele carriers tend to have more MACEs than non-A-allele carriers despite of ethnicity, that is 1.32-fold increase in East Asians (RR, 1.32; 95% CI, 0.99–1.77; P=0.06), 2.43-fold in Caucasians (RR, 2.43; 95% CI, 0.99–5.98; P=0.05), and 3.56-fold (RR, 3.56; 95% CI, 1.08–11.70; P=0.04) in American Africans. Conclusions: Our study indicates that the PEAR1 rs12041331 is prognostic in patients with ACS and/or PCI and treated with DAPT, which might be not caused by the associations with pharmacological response to antiplatelet agents. Further investigations are thus required to address the unrevealing mechanisms of PEAR1, especially on the development of atherosclerosis and the occurrence of acute adverse ischemic events. Funding Acknowledgement: Type of funding source: None